2024
DOI: 10.1038/s41408-023-00966-9
|View full text |Cite|
|
Sign up to set email alerts
|

GPRC5D as a novel target for the treatment of multiple myeloma: a narrative review

Paula Rodriguez-Otero,
Niels W. C. J. van de Donk,
Kodandaram Pillarisetti
et al.

Abstract: Multiple myeloma is a genetically complex and heterogenous malignancy with a 5-year survival rate of approximately 60%. Despite advances in therapy, patients experience cycles of remission and relapse, with each successive line of therapy associated with poorer outcomes; therefore, therapies with different mechanisms of action against new myeloma antigens are needed. G protein–coupled receptor class C group 5 member D (GPRC5D) has emerged as a novel therapeutic target for the treatment of multiple myeloma. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…A recent study shows that GPRC5D is a G protein-coupled receptor and a target for multiple myeloma treatment. Talquetamab targets GPRC5D and has shown efficacy in refractory multiple myeloma patients [ 73 ].…”
Section: Hematological Malignanciesmentioning
confidence: 99%
“…A recent study shows that GPRC5D is a G protein-coupled receptor and a target for multiple myeloma treatment. Talquetamab targets GPRC5D and has shown efficacy in refractory multiple myeloma patients [ 73 ].…”
Section: Hematological Malignanciesmentioning
confidence: 99%
“…Novel therapeutic anti-GPRC5D strategies, such as CAR-T cells and the first-in-class BsAb talquetamab, showed great efficacy with acceptable toxicity [82][83][84][85]. Regarding talquetamab, the updated results from the phase 1/2 MonumenTAL-1 trial (NCT03399799/ NCT04634552) showed a high and rapid ORR in the pivotal cohorts (74%, ≥VGPR: 59% at the dose of 405 µg/kg; 73%, ≥VGPR: 57% at the dose of 800 µg/kg), as well as in patients who had received prior T cell redirecting therapy (63%, ≥VGPR: 53%), without new safety concerns [83,86].…”
Section: T Cell Redirecting Therapy Targeting Non-bcma Antigensmentioning
confidence: 99%